Calogênese de pau-brasil (Caesalpinia echinata Lam.-fabaceae) in vitro visando a obtenção de um banco de germoplasma - Werner, Elias Terra (2009)
This work was carried out in order to study the callogenesis of C. echinatain vitro, through callus production, and the control of this process, by testing different culture media, sources of nitrogen and interaction between auxins and cytokinins, aiming the regeneration and conservation of the species. The induction of callus is the first step, in which leaf disks of brazilwood were used at different stages of development (juvenile, young and adult) combined with the growth regulators 2,4-D (0, 5, 10, 20, 50, 100 mg/L) and 6-BAP (2.0 mg/L) cultivated in MS culture medium. Juveniles leaves cultivated with low concentration of 2,4-D (5 and 20 mg/L) and young leaves treated with high concentrations of 2,4-D (50 and 100 mg/L) produced callus without significant differences between light and dark. The transfer of callus from MS culture medium with high concentrations of 2,4-D (5.0, 10.0 and 20.0 mg/L) to medium without growth regulators stimulated the formation of pro-embryonic masses (PEMs). Media free of growth regulators, 2.0 mg/L 2,4-D and 0.5 mg/L 2,4-D increased the number of embryogenic callus and pre-embryonic masses. Only on 0.5 mg/L 2,4-D structures similar to somatic embryos in globular stage and codiforme were observed. Different antioxidants were also tested (citric acid, ascorbic acid and activated charcoal) on young leaves of brazilwood in order to control the oxidation of the explants. The best results were provided by activated charcoal, however, inhibitory to callus. Response in growth of calluses of brazilwood was evaluated under the influence of different culture media (MS, B5, WPM and White), of different nitrogen sources and their interactions (NH4NO3, KNO3 and glutamine) and the interaction between auxins (2,4-D, IAA and IBA) and cytokinins (BAP and KIN). The explants used for these tests were callus of brazilwood, induced from juveniles leaves, inoculated in MS medium supplemented with 20 mg/L of 2,4-D. Fragments of approximately 0.1 g of fresh weight were used for the analysis of different culture media, effects of nitrogen compounds and the interaction of auxins and cytokinins. The analysis of fresh weight, on the experiments, were performed at 30 and 60 days after inoculation. At the end of each experiment (60 days) dry weight was determined. Regarding the media tested, MS, B5 and White did not differ statistically. However, the WPM media showed significantly different values compared to the other 3 media (MS, B5, White). A for the sources of nitrogen tested and their interactions, the treatment with a single source, NH4NO3, stimulated the best results after 60 days in culture. The interaction between auxins and cytokinin, in general, did not present statistical difference between treatments. However, treatments containing 2,4-D were the ones who produced callus with the highest fresh weight, in wich the concentration of 170.5 mg/L 2,4-D combined with 5.0 mg/L BAP gave better results. Histological analysis were carried out on callus, indicating that the formation of somatic embryos occured in callus of brazilwood. However, it was found that the callogenesis in brazilwood occurs on the adaxial surface of the leaf, as a result of proliferation of parenchymal cells. The callus showed colors ranging from dark yellow to brown, showing a friable aspect, not embryogenic, and accumulation of phenolic content. It was also observed the presence of meristematic areas (meristemoids), showing that callus of brazilwood were competent, but not embryogenic